2018
DOI: 10.1186/s12884-018-2043-3
|View full text |Cite
|
Sign up to set email alerts
|

Is the socioeconomic status of immigrant mothers in Brussels relevant to predict their risk of adverse pregnancy outcomes?

Abstract: BackgroundUnderstanding and tackling perinatal health inequities in industrialized countries requires analysing the socioeconomic determinants of adverse pregnancy outcomes among immigrant populations. Studies show that among certain migrant groups, education is not associated with adverse pregnancy outcomes. We aim to extend this analysis to further dimensions of socioeconomic status (SES) and to other settings. The objective of this study is to identify sociodemographic characteristics associated with advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 57 publications
2
29
0
1
Order By: Relevance
“…For example, Acevedo-Garcia et al [11] showed that foreign born status was associated with high odds of low birth weight among highly educated mothers and lower odds among mothers with low educational attainment. Similar patterns were observed for specific origins in Belgium [16].…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…For example, Acevedo-Garcia et al [11] showed that foreign born status was associated with high odds of low birth weight among highly educated mothers and lower odds among mothers with low educational attainment. Similar patterns were observed for specific origins in Belgium [16].…”
Section: Introductionsupporting
confidence: 82%
“…This regularity is referred to in the literature as the healthy immigrant effect [12,13] Although the healthy immigrant effect depends strongly on specific outcomes and the origins of the immigrants, a number of studies showed that immigrant status played a protective role in gropus which are particularly exposed to adverse socio-economic penalties. Specifically, some immigrant groups exhibited more favorable perinatal health outcomes when compared to natives and other immigrant populations even if they are more socioeconomically vulnerable [14][15][16]. In addition, there is evidence that the protective effect of immigrant status regarding specific indicators of perinatal healts variates across SES categories within the same immigrant groups.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that low SES in pregnant women can increase the risk of adverse pregnancy outcomes such as GDM, PTB, LBW and SGA [2][3][4][5][6][7]. However, others have suggested that SES indicators have little influence on pregnancy outcomes [7][8][9][10][11]. These contradictory findings shows that SES effects on pregnancy outcomes varied depending on pregnancy complications, countries, regions, races, especially on the SES indicators being examined.…”
mentioning
confidence: 99%
“…Most researchers have used a single SES indicator to reflect an individual's SES or used some SES indicators as proxies for others [13]. For example, pregnant women with lower education were more likely to suffer from GDM, PTB, LBW and SGA than those with higher education [4,5,7], whereas SES (education, occupation, and income) didn't influence the pregnancy outcomes for North African immigrants [11]. Others have investigated SES by using the community relevance information such as the household and context where a person resides [12,13].…”
mentioning
confidence: 99%
“…Some studies have shown that low SES in pregnant women can increase the risk of adverse pregnancy outcomes such as GDM, PTB, LBW, and SGA [2][3][4][5][6][7]. However, others have suggested that SES indicators have little influence on pregnancy outcomes [7][8][9][10][11]. These contradictory findings may reflect differences between countries, regions, or races.…”
mentioning
confidence: 99%